Improving Encapsulation of Hydrophilic Chloroquine Diphosphate into Biodegradable Nanoparticles: A Promising Approach against Herpes Virus Simplex-1 Infection - Tábata Loíse Cunha Lima; Renata de Carvalho Feitosa; Emanuell dos Santos-Silva; Alaine Maria dos Santos-Silva; Emerson Michell da Silva Siqueira; Paula Renata Lima Machado; Alianda Maira Cornélio; Eryvaldo Sócrates Tabosa do Egito; Matheus de Freitas Fernandes-Pedrosa; Kleber Juvenal Silva Farias; Arnóbio Antônio da Silva-Júnior (Pharmaceutics, 2018)
Chloroquine diphosphate (CQ) is a hydrophilic drug with low entrapment efficiency in hydrophobic nanoparticles (NP). Herpes simplex virus type 1 (HSV-1) is an enveloped double-stranded DNA virus worldwide known as a common human pathogen. This study aims to develop chloroquine-loaded poly(lactic acid) (PLA) nanoparticles (CQ-NP) to improve the chloroquine anti- HSV-1 efficacy. CQ-NP were successfully prepared using a modified emulsification-solvent evaporation method. Physicochemical properties of the NP were monitored using dynamic light scattering, atomic force microscopy, drug loading efficiency, and drug release studies. Spherical nanoparticles were produced with modal diameter of <300 nm, zeta potential of −20 mv and encapsulation efficiency of 64.1%. In vitro assays of CQ-NP performed in Vero E6 cells, using the MTT-assay, revealed different cytotoxicity levels. Blank nanoparticles (B-NP) were biocompatible. Finally, the antiviral activity tested by the plaque reduction assay revealed greater efficacy for CQ-NP compared to CQ at concentrations equal to or lower than 20 µg mL−1 (p < 0.001). On the other hand, the B-NP had no antiviral activity. The CQ-NP has shown feasible properties and great potential to improve the antiviral activity of drugs.